1988
DOI: 10.2307/2047130
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Endpoints of Chainable Continua

Abstract: ABSTRACT. An endpoint of chainable continuum is a point at which it is always possible to start chaining that continuum.Some endpoints appear to have the property that one is almost "forced" to start (or finish) the chaining at these points. This paper characterizes these "absolute endpoints", and this characterization is used to show that in a chainable continuum locally connected at p is equivalent to connected im kleinen at p. Introduction.Roughly speaking, an endpoint of a chainable continuum is a point at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The equivalence of conditions (l)-(4) has been stated in Rosenholtz's paper [9] as Proposition 1.3, p. 1309 for arc-like continua. However, the same proof is in fact valid for our more general setting, with the only change that the unique irreducible subcontinua between the points considered (the uniqueness is a consequence of the condition that each subcontinuum of an arc-like continuum is unicoherent, see [9], Theorem 0.0, p. 1306 and Lemma 1.2, p. 1308) are replaced by arbitrary ones which do exist by Theorem 1 of §48,1, p. 192 of the Kuratowski monograph [7]. The rest of the conclusion is a consequence of Theorem 20 of Thomas' paper [10], p. 28, where it is shown that local connectedness at a point, semi-local connectedness at a point, and aposyndeticity at a point with respect to any other point of a continuum coincide provided the continuum is irreducible.…”
Section: Lemma 31 If a Continuum Contains An Absolute End Point P mentioning
confidence: 93%
See 3 more Smart Citations
“…The equivalence of conditions (l)-(4) has been stated in Rosenholtz's paper [9] as Proposition 1.3, p. 1309 for arc-like continua. However, the same proof is in fact valid for our more general setting, with the only change that the unique irreducible subcontinua between the points considered (the uniqueness is a consequence of the condition that each subcontinuum of an arc-like continuum is unicoherent, see [9], Theorem 0.0, p. 1306 and Lemma 1.2, p. 1308) are replaced by arbitrary ones which do exist by Theorem 1 of §48,1, p. 192 of the Kuratowski monograph [7]. The rest of the conclusion is a consequence of Theorem 20 of Thomas' paper [10], p. 28, where it is shown that local connectedness at a point, semi-local connectedness at a point, and aposyndeticity at a point with respect to any other point of a continuum coincide provided the continuum is irreducible.…”
Section: Lemma 31 If a Continuum Contains An Absolute End Point P mentioning
confidence: 93%
“…A point p of an arc-like continuum X is called an absolute end point of X if p and X satisfy any of conditions (l)-(7) above. It is known from Rosenholtz's paper ( [9], Remark, p. 1310) that each absolute end point is an end point.…”
Section: N}} Is Contained In An E-neighborhood Of Pmentioning
confidence: 99%
See 2 more Smart Citations